A New Family of Degenerate Poly-Genocchi Polynomials with Its Certain Properties. (15th June 2021) - Khan, Waseem A.; Ali, Rifaqat; Alzobydi, Khaled Ahmad Hassan; Ahmed, Naeem
Abstract : In this paper, we introduce a new type of degenerate Genocchi polynomials and numbers, which are called degenerate poly-Genocchi polynomials and numbers, by using the degenerate polylogarithm function, and we derive several properties of these polynomials systematically. Then, we also consider the degenerate unipoly-Genocchi polynomials attached to an arithmetic function, by using the degenerate polylogarithm function, and investigate some identities of those polynomials. In particular, we give some new explicit expressions and identities of degenerate unipoly polynomials related to special numbers and polynomials.